Promoting the joy of teaching and learning in a diverse world - Omidire, M. F.; Aluko, F. R.; Mampane, R. M. (South African Journal of Higher Education, 2021)
Joy is a feeling that goes beyond happiness, and learning at whatever level should evoke joy in both students and teachers if its goals were to be met. However, the joy of learning may sometimes be totally excluded in a diverse world, especially in emerging economy contexts where issues of equality, equity and social justice are more profound. Using qualitative research methods and the theory of change as the theoretical framework, this study attempts to understand how joy can be promoted in learning despite the major complex diversities that often confront education in such emerging economy contexts. Findings indicate that explicit, implicit and hidden curriculum is key to realising the goals of learning. Furthermore, individuals from diverse settings want to be included in their own education and want their identity, culture, language and life experiences to form part of what is being learned. The participants believe that technology is critical to achieving the joy of learning in the 21st century and beyond. Recommendations include redesigning the curricula at various education levels to make it more relevant and inclusive and returning to the emotional aspects of teaching and learning. Higher education institutions have a critical role to play in achieving a paradigm shift in the training of preservice teachers. We advance further areas of research.